Effect of the reduction of silver ions to silver nanoparticles on the dielectric properties of chitosan-silver triflate electrolyte - Aziz, Shujahadeen B.; Abidin, Zul Hazrin Zainal; Arof, Abdul Kariem (2009)
Films of solid polymer electrolyte based on chitosan and silver triflate (AgCF3SO3) have been prepared by casting technique. As a confirmation, the UV-vis results show the temperature dependence of silver nanoparticles. The dielectric constant increases with increasing salt concentration. The dielectric constant and dielectric loss curves show the higher values in the low frequency region and they are almost constant at higher frequencies. The dielectric constant and dielectric loss values are decreased above 358 K, as a result of transformation from silver ion to silver nanoparticles. The loss tangent peaks are broad and their heights decrease above 358 K. The broadness of loss tangent peaks indicates the distribution of relaxation time.